High-performance polymer field-effect transistors fabricated with low-bandgap DPP-based semiconducting materials. Issue 36 (16th July 2015) - Mao, Zupan; Zhang, Weifeng; Huang, Jianyao; Shi, Keli; Gao, Dong; Chen, Zhihui; Yu, Gui
Abstract : New π-conjugated D–A copolymersPDMOTT- n combining a diketopyrrolopyrrole unit and a 3, 6-dimethoxythieno[3, 2- b ]thiophene moiety were synthesized, and their field-effect performances were successfully characterized. Abstract : A series of new π-conjugated D–A copolymersPDMOTT- n ( n =118, 122, 320, and420 ) containing a diketopyrrolopyrrole unit and a 3, 6-dimethoxythieno[3, 2- b ]thiophene moiety was designed and synthesized, and their field-effect properties were characterized. The polymersPDMOTT- n have a low bandgap of 1.27 eV and exhibit a broad absorption. Solution-processed field-effect transistors based on these polymers were fabricated with a bottom-gate/bottom-contact configuration and demonstrated typical p-type charge transporting properties. Of these, PDMOTT-420 with the longest alkyl side chains and having the longest distance between the branching point of the alkyl side chain and π-conjugated backbone of the polymer, exhibited the best carrier transporting performance with a hole mobility of 2.01 cm 2 V −1 s −1 and with an on/off current ratio of 10 4 –10 5 . The characterization results of grazing incidence X-ray diffraction and tapping-mode atomic force microscopy showed that the thin film of the polymerPDMOTT-420 forms larger grains and more useful nanofibrillar intercalated structures and owns shorter π–π stacking distance and better crystallization than those of another three polymers. These results could help us to better understand the structure–property relationship of polymer semiconductors and to design novel π-conjugated polymers for high-performance field-effect transistors.